JUEGO DIDÁCTICO EN EL MEJORAMIENTO DEL DESARROLLO DE DESTREZAS EN LOS NIÑOS DE EDUCACIÓN INICIAL NIVEL II - BERMEO MURILLO NAGELY ELIZABETH (2024)
The following research project is based on the didactic game and the development of skills of children in Initial Education level II. The little practice of these games in the teaching of children at the Emigdio Esparza Moreno Educational Unit is stimulated as a problematic situation. Among the didactic games we can mention role-playing games, memory games, and singing and movement games, which benefit children. Children by promoting learning, developing their creativity and imagination, and contributing to improving fine motor skills and guessing. The main objective of our research is to propose educational games as a support tool for improving the development of skills in children, increasing motivation, attention, and memory. It also emphasizes the needs of using appropriate educational games within the teaching process and learning. The theoretical information base emphasizes educational games and, in turn, the development of children’s cognitive abilities and skills. The international and local information reflected in the research confirms the influence and importance of didactic games in learning. Through qualitative research we observe the educational reality, supported by descriptive and documentary research. The results obtained in the research will contribute to improving learning and creating a pleasant environment for children in Initial Education level II.